Book Review: Red Skin, White Masks: Rejecting the Colonial Politics of Recognition - Nahanee, Michelle Lorna (Stream: Interdisciplinary Journal of Communication, 2014)
Red Skin, White Masks: Rejecting the Colonial Politics of Recognition by Glen Sean Coulthard was launched on Oct. 22nd, 2014 at SFU Woodwards. For more information regarding the book launch and its panel discussion, please visit the event’s page. The book examines anti-Ââ€colonial efforts of Indigenous resurgence in Canada from 1969 to the present and demonstrates the shift from tradition-Âbased assertions of land and title to negotiated claims for land and recognition. It strips the promise of emancipation from the pursuit of recognition and offers Five Theses on Indigenous Resurgence and Decolonization. READ a book review by Michelle Lorna Nahanee, a member of the Squamish Nation and MA student in Global Communications.